Requirements to Improve the Technical Support at Umm Al-Qura University (2019) (Concept Proposal) - Alqahtani, Reem Metlea Mohamed; Almarghlani, Reham Zahir Omar (Journal of engineering sciences and information technology, 2024)
This paper aims to examine the requirements for improving technical support services at Umm Al-Qura University in 2019, focusing on all stakeholders who benefit from these services, including (faculty members, students, and administrative staff) and the technical support team. To gather insights on the challenges faced by these stakeholders, the study employed two methods: direct interviews with experts and electronic surveys. The findings revealed several issues, including difficulties in communication between beneficiaries and technical support, a lack of documentation regarding the support team's activities, and an inability to assess beneficiary satisfaction with the provided services. In response to these challenges, the proposed concept is the development of a mobile application designed to facilitate requests for technical support, thereby enhancing communication among all stakeholders and the technical support team. This application will provide numerous benefits, such as documenting the workflow of the support team, which will allow for the analysis of performance, productivity, and verification of user satisfaction. Additionally, the application aims to streamline the educational process and create a learning environment equipped with effective technological solutions, backed by a dedicated technical support team, The researcher recommends Implementing a user-friendly smartphone application for requesting technical support, Organizing specialized training sessions on how to use the application for technical support services and Providing internet access across the university to facilitate technical support requests when needed.
Keywords: Technical Support; Technical Assistance; Improvement; Implementation